Limited Effect of Indolamine 2,3-Dioxygenase Expression and Enzymatic Activity on Lupus-Like Disease in B6.Nba2 Mice - Davison, Laura M.; Liu, Jessica C.; Huang, Lei; Carroll, Thomas M.; Mellor, Andrew L.; Jørgensen, Trine N. (Frontiers in Immunology, 2019)
B6.Nba2 mice spontaneously develop a lupus-like disease characterized by elevated levels of serum anti nuclear autoantibody (ANA) immune complexes and constitutive type I interferon (IFNα) production. During disease progression, both plasmacytoid dendritic cells (pDCs) and antibody secreting plasma cells accumulate in spleens of B6.Nba2 mice. Indoleamine 2,3-dioxygenase (IDO) has been suggested to play a role in several autoimmune diseases including in the MRL/lpr model of mouse lupus-like disease; however, it remains unknown if IDO is involved in disease development and/or progression in other spontaneous models. We show here that IDO1 protein and total IDO enzymatic activity are significantly elevated in lupus-prone B6.Nba2 mice relative to B6 controls. Neither pharmacologic inhibition of total IDO nor IDO1 gene ablation altered serum autoantibody levels, splenic immune cell activation pattern, or renal inflammation in B6.Nba2 mice. Interestingly, IDO pharmacologic inhibition, but not IDO1 deficiency, resulted in diminished complement factor C’3 fixation to kidney glomeruli, suggesting a possible therapeutic benefit of IDO inhibition in SLE patients with renal involvement.